2022
DOI: 10.20473/mog.v30i22022.52-57
|View full text |Cite
|
Sign up to set email alerts
|

The performance of midwives in early detection of cervical cancer using visual inspection test with acetic acid

Abstract: HIGHLIGHTS 1. Visual Inspection with Acetic Acid (VIA) method is used in midwifery for early detection of cervical cancer.2. Service period, knowledge, and attitudes are factors that affect a midwife's performance in using VIA method for cervical cancer detection.   ABSTRACT Objective: This study examined the association between service period, knowledge, and attitudes toward the performance of midwives in the early detection of cervical cancer using the Visual Inspection with Acetic Acid (VIA) method in Banja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Our research is in line with Sari et al in 2022. Showed the associations between the service period (p = 0.005), knowledge (p = 0.0001), and attitude (p = 0.005) with the performance of midwives in the early detection of cervical cancer using the VIA method.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our research is in line with Sari et al in 2022. Showed the associations between the service period (p = 0.005), knowledge (p = 0.0001), and attitude (p = 0.005) with the performance of midwives in the early detection of cervical cancer using the VIA method.…”
Section: Discussionsupporting
confidence: 82%
“…The research results show no connection Between education and a relationship between training status and knowledge of midwives in detecting early cancer cervix using the VIA method in Banjarmasin City. Training is one step that becomes a consideration in increasing the performance of midwives in detecting cervical cancer (Sari, Lestari and Mulawardhana, 2022). Research by Mardiana et al revealed that years of service correlated with the behavior of midwives in conducting IVA screening (Mardiana, Dasuki and Pradjatmo, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The accessibility of health information is a determining factor in the level of knowledge and attitudes, ultimately influencing the behavior of women of childbearing age. 43,44 The E-Duva application streamlines access to information and education, eliminating the need for physical visits to healthcare facilities. It requires a one-time download and can be used offline.…”
Section: Discussionmentioning
confidence: 99%